Hubungan Antara Kualitas Ridur dan Aktivitas Fisik dengan Siklus Menstruasi pada Remaja Putri di SMAN 5 Bandar lampung - Amir, Anzela; Sari, Ratna Dewi Puspita; Utama, Winda Trijayanthi; Berawi, Khairun Nisa (Medula, 2024)
Menstruation is a natural process in which the inner uterine lining of the uterus is regularly released every month in women. The most vulnerable period for a person to experience menstrual disorders is during the first year, about 75% of adolescent girls experience menstrual disorders. According to the World Health Organization (WHO), 75% of adolescent girls experience menstrual cycle disorders. Risk factors that can cause disruptions in the menstrual cycle include hormonal imbalances due to environmental stressors and excessive physical activity and low energy intake. In addition, exposure to pollutants such as cigarette smoke, stress, depression, short sleep, Body Mass Index (BMI), and certain medical conditions can also affect the menstrual cycle. This study is an analytical study with cross-sectional design. The study was conducted at SMAN 5 Bandar Lampung in October - December 2023. The research instruments used in this study were questionnaires to assess sleep quality, namely PSQI, questionnaires from who, namely GPAQ to measure physical activity, and menstrual cycle questionnaires to assess menstrual disorders in respondents. Chi-square test results with a confidence level of 95% showed a p-value of 0.265 (p-value > 0.05) on sleep quality variables and p-value of 0.006 (p-value < 0.05) on physical activity variables. There is no relationship between sleep quality and physical activity with the menstrual cycle in adolescent girls at SMAN 5 Bandar Lampung in 2023. There is a relationship physical activity with the menstrual cycle in adolescent girls at SMAN 5 Bandar Lampung in 2023.